Graves' disease in children: long‐term outcomes of medical therapy. (14th June 2016) - Rabon, Shona; Burton, Amy M.; White, Perrin C.
Summary: Background and objectives: Management options are limited for the treatment of Graves' disease, and there is controversy regarding optimal treatment. We describe the demographic and biochemical characteristics of children with Graves' disease and the outcomes of its management. Methods: This is a retrospective study reviewing medical records from 2001 to 2011 at a tertiary‐care paediatric hospital. Diagnostic criteria included elevated free T4 and total T3, suppressed TSH, and either positive thyroid‐stimulating immunoglobulin or thyroid receptor antibodies or clinical signs suggestive of Graves' disease, for example exophthalmos. Patients were treated with antithyroid drugs (ATD), radioactive iodine, or thyroidectomy. The main outcome measures were remission after medical therapy for at least 6 months and subsequent relapse. Results: A total of 291 children met diagnostic criteria. A total of 62 were male (21%); 117 (40%) were Hispanic, 90 (31%) Caucasian, and 59 (20%) African American. Mean age (±standard deviation) at diagnosis was 12·3 ± 3·8 (range 3–18·5) years. At diagnosis, 268 patients were started on an antithyroid drug and 23 underwent thyroid ablation or thyroidectomy. Fifty‐seven (21%) children achieved remission and 16 (28%) of these patients relapsed, almost all within 16 months. Gender and ethnicity did not affect rates of remission or relapse. Of 251 patients treated with methimazole, 53 (21%) had an adverse reaction, including rash, arthralgias, elevated transaminases, or neutropenia. Conclusions: Most children with Graves' disease treated with ATD do not experience remission, but most remissions do not end in relapse. Adverse reactions to methimazole are common but generally mild.